Tolerance Values Education in Javanese Traditions in Baru Manis Village - Eka Yanuarti; Azm Eliza (CV Media Inti Teknologi, 2023)
Baru Manis village community has three beliefs, namely Islam, Christianity, Sapta Darma, these three beliefs are tolerant of each other in tradition. So, that the aim of the researcher is to find out the forms, values, and implementation of traditions that exist in the Baru Manis community. This study uses a qualitative descriptive approach. The data sources are primary and secondary. This research data collection method is observation, interviews and documentation. Data analysis techniques are data collection, data reduction, presentation, drawing conclusions/verification and triamulation. The results of this study indicate that, First, the forms of tradition that exist in Baru Manis Village, namely the salvation tradition, the Suronan Tradition, the wedding ceremony tradition, the Kenduri tradition, the tradition of giving birth to babies and the tradition of visiting graves. Second, the Values, namely Growing Empathy Between Religions, Growing Cooperation Between Religions, high principles of mutual cooperation and mutual empathy. Third, the implementation of the tradition, namely salvation is carried out to get the blessing of God, the Suronan Tradition. The contents of this ceremony are generally saying prayers to God, the tradition of the wedding ceremony is to determine auspicious days, put on tarub, get married and celebrate.